PRODUCTIONS AND CULTURAL PRODUCTS IN THE CLASSROOM: A CRITICAL-DIALOGICAL ANALYSIS OF THE HARRY POTTER FANDOM AND DESPICABLE ME FRANCHISE - Paula, Luciane de [UNESP]; Maia Baris, Ana Beatriz [UNESP]; Oliveira, Natasha Ribeiro de [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
This article aims to think of cultural productions, transformed into consumer products, in the classroom, as dialogic strategies of critical formation. The proposal is to reflect on the presence of these productions and products from two iconic works of the cultural industry for their virality: Harry Potter and Despicable Me - the world's largest fandom community and the success of minions, specifically in Brazil. The theoretical foundation is based on Bakhtinian studies in dialogue with critical theory. Harry Potter will be thought through the production of fans and Despicable Me in the fields from the image of the minions. It is intended to think about the relationship between school and society, as well as about the constitution of school life as a citizen formation, and this is its relevance.
Keywords: Critical theory; Bakhtinian studies; Dialogue; Convergence of culture; Transmedia